Brain Drain or Brain Exchange? - Hayden Glass; Wai Kin Choy (New Zealand Government, The Treasury, 2001)
This paper explores the "brain drain" hypothesis – the idea that New Zealand is losing many of its most talented citizens to other countries. We conclude that we are experiencing more of a brain exchange than a brain drain. There have been net outflows of New Zealand citizens for forty years, and we have been replacing those leaving with non-New Zealand citizens. On the basis of the data available, our immigrants appear to be more skilled than our emigrants (and than our general population). But there may be some cause for concern if immigrants cannot get jobs to make use of their skills. Migration flows to and from Australia are different from those with the rest of the world. New Zealand consistently loses its citizens to Australia, but they are not just the highest skilled. Instead, they are representative of the general population of New Zealand. That is, there is no brain drain to Australia either, but what might be called a "same drain". This is likely to be a consequence of the common labour market. Policy responses could focus on both outflows and inflows. Limited policy levers exist for attracting and retaining New Zealand citizens within the country, other than making the country a more attractive place to work, and live. The key policy issue for inflows is the improvement of the selection, settlement, and integration of immigrants. The paper ends by calling for a more sophisticated debate on immigration and emigration, and a more accurate conception of what will be an ongoing trend – that is, the increasingly free flow of people (including New Zealanders), around the globe.
Keywords: F22; O15; 330; International migration; brain drain